Analisis Keragaman Genetik 21 Genotipe Teh [Camellia sinensis (L.) O. Kuntze] Berdasarkan Penanda RAPD - Budi Martono; Syafaruddin Syafaruddin (Jurnal Tanaman Industri dan Penyegar, 2018)
Knowing the genetic diversity in the tea germplasms collection is one of important conditions for assembling new superior varieties. Information of genetic diversity can be obtained through analysis using RAPD molecular markers. The study aimed to determine the genetic diversity of 21 tea genotypes based on RAPD markers. The research was conducted in Integrated Laboratory, Seameo Biotrop, Bogor, from July to September 2013. Genomic DNA was isolated from 21 tea genotypes leaf samples, then amplified with primer OPA 03, OPA 05, OPB 04, OPB 06, OPC 06, and OPD 08. Electrophoresis result was converted into binary data. The genetic similarity and cluster analysis calculation was done using NTSYS-pc version 2.10. In this research, 50 polymorphic bands (94,34%) and 3 monomorphic band (5,66%) were obtained. Cluster analysis based on Nei's genetic distance using the unweighted pair-group method with arithmatic (UPGMA) divided 21 tea genotypes into two groups at a genetic similarity value of 0,48. Group 1 consisted of 20 tea genotypes, while the second group comprised only a one genotype (Sin 27). The range of genetic similarity matrix was between 28%–92%, the lowest genetic similarity (28%) was found between GMB 4 and Sin 27 genotypes, while the highest (92%) was found between AS 2 and AS 1 genotypes. The information obtained can be utilized in breeding programs with the support of agronomic characters as well as in the conservation of tea germplasm.